(untitled) (Vietnam Journal of Community Medicine, 2025)
Subjects and Methods: Identify some factors related to hospital-acquired infections in the Intensive Care Department of Nghe An Obstetrics and Children’s Hospital in 2024. Results: Among 306 patients meeting research criteria in 3 intensive care units, the rate of hospital-acquired infections was 10.8%. Factors related to the possibility of hospital-acquired infections include: Age, area of ​​residence, gestational age at birth, presence of underlying/chronic diseases, length of treatment in the intensive care unit length and number of invasive interventions/procedures on patients with p<0.05. Treatment results: Patients with hospital-acquired infections are at risk of more serious complications during treatment (p<0.05). Conclusion: The rate of hospital-acquired infections is 10.8%. Factors related to the possibility of hospital-acquired infections include: Age, area of ​​residence, gestational age at birth, presence of underlying/chronic diseases, length of treatment in the intensive care unit length and number of invasive interventions/procedures on the patient (p<0.05). Patients with hospital-acquired infections are at risk of more serious complications during treatment with p < 0.05.